Archaeological evidence of anthropogenic burning for food production in forested uplands of the Grand Canyon province, northern Arizona - Sullivan, Alan P.; McNamee, Calla; Wendel, Martha; Mink, Philip B.; Allen, Susan E. (Frontiers in Environmental Archaeology, 2024)
Despite convincing archaeological arguments about the global effects of human pyrogeography and their evolutionary significance, many of the implicated data sources are unavailable in research contexts that lack significant accumulations of charcoal or stands of fire-scarred trees.In view of the strong likelihood that hominins routinely ignited small, low-intensity landscape fires for millennia, we explore the role of cultural burning for food-production in an area of the American Southwest where anthropogenic fire has not been considered. To illustrate the virtues of a multidisciplinary approach, informed by Formation Theory and time perspectivism, we focus on the returns from macrobotanical and palynological analyses of samples recovered from a variety of archaeological and geoarchaeological contexts in the Upper Basin, a landform located south of the Grand Canyon in northern Arizona. Previous archaeobotanical studies of samples recovered from archaeological sites (ca. AD 500-1500) in the basin's pinyon-juniper woodlands are dominated by amaranth, chenopodium, and other economic ruderals. These findings support the "fire foodway" model that posits prehistoric Indigenous populations of the Upper Basin depended on these fire-following wild plants, rather than maize, by harvesting their abundant seeds and leaves from production locations that were created by low-intensity understory fires. In this paper, we present the results of new studies of archaeobotanical remains recovered from cut-back terraces and sedimentary contexts that (i) expand the evidence base for the fire-foodway model, (ii) provide a basis for proposing several types of prehistoric cultural burning practices, and (iii) introduce the outlines of the ruderal seed-bed hypothesis. Combined, these findings provide a new archaeological perspective on upland subsistence practices in the northern American Southwest. Our study also highlights biases of modern vegetation surveys that do not include archaeological data, and contributes to an appreciation of the extent to which biodiversity has declined because of widespread fire exclusion.